THEORETTCAL APPROACH TO THE ATTENUATION COEFFICIENT OF LIGHT IN SEA WATER - Murty, A V S (Indian Journal of Fisheries, 2011)
The attenuation coeflScient of sea water is derived from a formula which is more general than the Lambert’s equation. The mean attenuation coefficient which the Secchi disc observations give is obtained therefrom. The constant of the Secchi disc is discussed in the light of the relationship developed. The theoretical concept developed here, falls in accordance with the expressions based on field data.